PATTERN OF HEALTH CARE EXPENDITURE OF PRIVATE AND PUBLIC: A CASE STUDY OF HOSPITAL PATIENTS IN KANNUR DISTRICT, KERALA, INDIA - P, Maneesh; EL ALAOUI, Aicha (International Journal of Research -GRANTHAALAYAH, 2018)
In Kerala, the disturbing trend is that the public health care system is getting alienated from the people since 1980’s. About 30% of the lower income families seeks medical service from the government hospitals. This is because of the fall in the quality of the services of the government hospitals. In the present situation, the rate of utilization of the private sector can be increased drastically pointing to the poor performance of the public health care system. The government hospital has some problems like poor physical or infrastructure facilities, ineffective leadership and unsatisfactory supply of drugs and medical supplies faculty of staffing procedure. These above stated problems do not exist in private hospitals. Therefore, the present study carried out to assess the healthcare expenditure of government and private hospitals patients in Kannur district. The study was conducted during 2015-16. The sample size of the survey contains a total of 120 respondents from Kannur district. The study analyses the interrelationship between health care expenditure and major socioeconomic factors such as monthly income, age, gender, marital status and occupation. The health care expenditure divided into two-direct and indirect health care cost. The direct health care cost includes- user fee charge, medical charge, diagnostic charge and surgical cost. The indirect health care cost comprises of transportation charge, food and bevarages charge and accommodation charges. The study found that the direct cost of health care is high in both private and public sector hospitals. Finally, the study suggests that an initiative along the role of government is requested to secure the health demands of poor as health care costs are growing over time.